2010
DOI: 10.1614/ws-d-09-00005.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Effective Methods for Breaking Seed Dormancy in Buffalobur (Solanum rostratum)

Abstract: The spread of buffalobur in China poses a serious threat to existing ecosystems, and control and eradication of this species have become increasingly important. Studies were carried out to ascertain the seed production, morphological characterization, dormancy behavior, and methods for breaking dormancy of buffalobur. The results showed that a single buffalobur plant could produce 1,600 to 43,800 seeds with an average weight of 3.0 mg. Average seed length, width, and thickness were 2.5, 2.0, and 1.0 mm, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
1
26
0
3
Order By: Relevance
“…Chauhan et al (2006b) found that the germination rate of Oriental mustard (Sisymbrium orientale) seeds increased in direct proportion to increasing concentrations of KNO 3 , although only up to 0.02 M, after which it decreased. Promotion and inhibition of germination at low and high concentrations of KNO 3 have previously been reported by Wei et al (2010) and Foley & Chao (2008), in different plants.…”
Section: Knomentioning
confidence: 56%
“…Chauhan et al (2006b) found that the germination rate of Oriental mustard (Sisymbrium orientale) seeds increased in direct proportion to increasing concentrations of KNO 3 , although only up to 0.02 M, after which it decreased. Promotion and inhibition of germination at low and high concentrations of KNO 3 have previously been reported by Wei et al (2010) and Foley & Chao (2008), in different plants.…”
Section: Knomentioning
confidence: 56%
“…In this respect, seed soaking for 12-24 h is known to be an efficient means for improving the germination of Solanum species (Hayati et al, 2005;Ahmed et al, 2006), as it may remove seed germination inhibitors (Bewley et al, 2013). Similarly, applications of the plant growth regulator GA 3 or KNO 3 are efficient at releasing Solanum seeds from dormancy and stimulating germination (Hayati et al, 2005;Wei et al, 2010;Gisbert et al, 2011a). Light irradiation, which is an important regulator of seed germination in solanaceous species (Koo et al, 2015), has also been observed to be efficient at stimulating germination in S. torvum seeds.…”
Section: Tablementioning
confidence: 99%
“…This characteristic has even led to the proposed use of vegetative propagation to overcome the seed germination problem (Miceli et al, 2014). The breaking of dormancy, which is a common phenomenon among wild Solanum species (Taab and Andersson, 2009;Wei et al, 2010;Kandari et al, 2011;Tellier et al, 2011), and the enhancement of germination can be achieved using combinations of many different physical (e.g., seed soaking, manual scarification, cold stratification, heat shocks, light irradiation, and magnetic fields) and/or chemical (e.g., scarification with acidic or basic chemicals, plant growth regulators, and osmotic treatments) treatments (Finch-Savage and Leubner-Metzger, 2006;Bewley et al, 2013;Holubowicz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, applications of GA 3 or KNO 3 were also efficient for other Solanum species (Hayati et al 2005, Wei et al 2010, Gisbert et al 2011.…”
Section: Research Notementioning
confidence: 99%